TAX PREFERENCES IN THE FUNCTIONING OF BUSINESS ENTITIES DURING THE RUSSIAN-UKRAINIAN WAR - PIKHNYAK, Tatiana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the importance of the functioning of small business as one of the important sectors of the economy during the Russian-Ukrainian war. Their activities in partially occupied, front-line, support and safe regions were studied, in particular: the number of registered individual entrepreneurs, active individual entrepreneurs, individual entrepreneurs who ceased their activities in 2021-2023. State support measures for small business entities were considered: direct payments from the budget, tax preferences, preferential loans, measures to reduce administrative pressure. Attention is focused on one of the types of support for business entities during martial law - tax preferences. Their role and importance in the activities of enterprises that are on the simplified taxation system is determined and the importance of the mentioned support is proven. It is accepted to pay attention to the current tax legislation - the Tax Code of Ukraine regarding preferences for the simplified tax payers of the first, second and third groups. The tax preferences for four groups of taxpayers who are on the simplified taxation system in 2022 were considered according to the following indicators: the maximum amount of income per year, the rate of a single tax, the amount of a single contribution (per month), documentary checks, sanctions for violating tax legislation and non-use of cash registers (registrars of settlement transactions). The revenues and expenditures of the budget in 2021-2022 and their impact on the country’s economy were analyzed. Problems of the development of small enterprises in Ukraine and ways of increasing the efficiency of their activities in modern market conditions are highlighted: introduction of tax incentives for local production of important products in Ukraine; exemption from taxation of materials and equipment necessary for the modernization of production; preferences for relocated enterprises or those that continue to employ internally displaced persons; formation of additional credit support programs for business entities.